Adsorption kinetics, mechanism, isotherm, and thermodynamic analysis of copper ions onto the surface modified agricultural waste. Issue 1 (26th December 2012) - Senthil Kumar, P.; Senthamarai, C.; Durgadevi, A.
<x xml:space="preserve">Abstract</x> The adsorption of copper ions onto the surface modified Strychnos potatorum seeds (SMSP) in a batch adsorption system has been studied. Kinetics, mechanism, isotherm, and thermodynamic parameters have been estimated. Adsorption kinetics of copper ions onto the SMSP follows a pseudo‐second order kinetic model. Adsorption mechanism was explained with the intraparticle diffusion model, Boyd kinetic model (BKM), and Shrinking core model (SCM). Adsorption process was found to be controlled by both intraparticle diffusion and film diffusion. The diffusivity values were estimated from the BKM and SCM. Adsorption isotherm data agreed well with the Freundlich adsorption isotherm model, which indicates the multilayer adsorption of copper ions onto the SMSP. The maximum monolayer adsorption capacity of the SMSP was found to be 248 mg of copper ions/g of SMSP. Adsorption thermodynamic studies show that the adsorption of copper ions onto the SMSP was spontaneous and exothermic in nature. © 2012 American Institute of Chemical Engineers Environ Prog, 33: 28–37, 2014